Post-induction treatment for acute myeloid leukemia: something change? - Jaramillo Segura, Sonia; Schlenk, Richard Friedrich (Current oncology reports, 2021)
Until recently, improvement in terms of survival for patients with acute myeloid leukemia (AML) was achieved mostly in younger patients with dose intensification of conventional chemotherapy and a broadening use of allogeneic hematopoietic cell transplantation (allo-HCT) whereas the results remained dismal and very stable in patients older than 60 years. The current review highlights the recent developments in standard intensive post-remission chemotherapy, evidence for the use of recently approved agents, and discusses the relevance of measurable residual disease (MRD) measurement in treatment adaptation.